If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2x + -12 = x + 7 Reorder the terms: -12 + x + 2x = x + 7 Combine like terms: x + 2x = 3x -12 + 3x = x + 7 Reorder the terms: -12 + 3x = 7 + x Solving -12 + 3x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + 3x + -1x = 7 + x + -1x Combine like terms: 3x + -1x = 2x -12 + 2x = 7 + x + -1x Combine like terms: x + -1x = 0 -12 + 2x = 7 + 0 -12 + 2x = 7 Add '12' to each side of the equation. -12 + 12 + 2x = 7 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 7 + 12 2x = 7 + 12 Combine like terms: 7 + 12 = 19 2x = 19 Divide each side by '2'. x = 9.5 Simplifying x = 9.5
| 8j-5+j=14.2 | | -5(4y-8)+4(3y+8)= | | 9x+45=3x+27 | | 27=18.9+x | | 17x=-3/4 | | .25o+3.00=5.50 | | 5*2x=18 | | 6/21+5/28 | | .08m+17.00=31.80 | | 3m+4=q | | 11/12-3/8 | | 3(2x-1)-4(x+7)= | | 8x^4-x=0 | | 3/15+2/5 | | 12x+4x-5-7=20 | | 3/7+1/5 | | 5x-(2x-3)=17-4x | | 3/5x-8=22 | | -7u+13=-4(u-7) | | 5/11+2/9 | | 3/38=x/32 | | n/3+5+7 | | 8x-64=6x-54 | | (9/5)x-2= | | 2/5X+4=20 | | (3x-6)*(2x-4)=6x-26 | | 3/5+1/6 | | 7/9-2/3 | | 0.3+0.4x+x=2x-10 | | 6/7x1/6 | | 3x-2x=-18 | | -3(5y-10)+2(4y+8)= |